The Invention of Ancient Israel: The Silencing of Palestinian History - Whitelam, Keith W. (Taylor and Francis, 2013)
The Invention of Ancient Israel shows how the true history of ancient Palestine has been obscured by the search for Israel. Keith W. Whitelam shows how ancient Israel has been invented by scholars in the image of a European nation state, influenced by the realisation of the state of Israel in 1948. He explores the theological and political assumptions which have shaped research into ancient Israel by Biblical scholars, and contributed to the vast network of scholarship which Said identified as 'Orientalist discourse'.This study concentrates on two crucial periods from the end of the late Bronz